Industrial quality and resistance to spot blotch and scab in triticale, wheat and rye - de Oliveira, Andréia M. Rotta; Baier, Augusto Carlos (Pesquisa Agropecuaria Brasileira, 1993)
In the south of Brazil, where climatic conditions are unfavorable for small grain cultivation, triticale is considered as an alternative crop. Microsedimentation (MS) test using sodium dodecyl sulphate, Hagberg falling numbers (FN) and resistance to scab (Fusarium graminearum) and to spot blotch (Bipolaris sorokiniana) were evaluated in nineteen triticale genotypes, three wheat cultivars, and one rye cultivar, in four sowing dates, in 1989, in Passo Fundo, RS, Brazil. Resistance to scab and spot blotch was highest in rye BR-1. Following rye, the triticale genotypes, TCEP 887, IAPAR 23-Arapoti, IAPAR 38-Araruna, CEP 22-Botucaraí, PFT 8913, CEP 25, PFT 8812, TCEP 852, PFT 8613 "S", PFT 882 e PFT 8811, showed a good resistance to spot blotch, whereas PFT 8812, PFT 8913, CEP 25, PFT 882 and Triticale BR-2 had better resistance to scab. The three wheat cultivars presented the highest FN and MS values, rye had intermediate values and the triticale genotypes where considered unsatisfactory. In average, later sowing contributed to increase grain quality.